Genetic control of potassium content of common bean seeds - Poersch, Nerison Luís; Ribeiro, Nerinéia Dalfollo; Rosa, Daniele Piano; Possobom, Micheli Thaise Della Flora (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to investigate possible maternal effects on potassium content of common bean seeds, as well as to estimate the heritability and selection gains in early hybrid generations for this character and to evaluate the efficiency of genetic selection to improve the nutritional quality of common bean (Phaseolus vulgaris). Crosses with four cultivars from the Mesoamerican gene pool yielded the reciprocal F1 and F2 generations and the backcrossed populations (BCP1 and BCP2). The potassium content of the progenies was measured via nitric‑perchloric digestion and flame photometry. The potassium content in the tested progenies varied from 6.0 to 14.9 g kg-1 dry matter, and no significant maternal effect was observed. The narrow-sense heritability ranged from low (33.26%) to intermediate (43.05%). Partial dominance was observed for low potassium content in the seeds. No increase in potassium content was obtained through selection. Breeding common bean plants for increasing potassium content in seeds may be difficult because the local environment strongly influences the character.